Induksi Kalus Sisik Umbi Lilium longiflorum Thunb. oleh Auksin dan Sitokinin, serta Respons Pertumbuhannya Secara In Vitro: Induksi Kalus Sisik Umbi Lilium longiflorum Thunb. oleh Auksin dan Sitokinin, serta Respons Pertumbuhannya Secara In Vitro - Yeni Ekawati; Apriliana Dyah Prawestri; Eddy Nurtjahya; Anggraeni Anggraeni (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2022)
Lilium longiforum Thunb.is a potential ornamental plant that has been developed in several indusrtry, such as pharmaceutical industry and floriculture industry. Generative propagation of L. longiflorum is difficult and more effective when propagated asexually through tissue culture techniques. This research aimed to analyze callus induction from L. longiflorum bulb scale and its growth response to the addition of auxin and cytokinin in culture media. This research were tested in two treatments: MS + 3.0 mg L-1 2.4-D + 0.5 mg L-1 BAP, incubated in dark condition for 24 hours (treatment 1) and MS + 1.5 mg L-12.4-D + 1.0 mg L-1BAP, photoperiod 16/8 h (treatment 2). Furthermore, calli were planted on regeneration media (MS + 3.4 mg L-1BAP + 0.09 mg L-1NAA). The result showed that explant in treatment 2 (MS + 1.5 mg L-12.4-D + 1.0 mg L-1BAP, photoperiod 16/8 hours dark/light) is more responsive than treatment 1 on callus induction and subculture treatment. This treatment also produced good quality of calli which were shown in a compact texture, yellowish green colour and 100% survived. Regeneration media succeeded in regenerating calli into indirect shoots by 100%, even though no direct shoots and roots were found in this experiment. This research suggest that treatment 2 can used as an effective protocol on developing L. longiflorum.